Castles and the Biography of Place: Boundaries, Meeting Places and Mobility in the Sussex Landscape. (2nd January 2019) - Jamieson, Elaine
ABSTRACT: This paper explores the influence of antecedent landscapes on the placement of medieval castles in Sussex. It considers the relationship between castles and major physical features of the pre-Conquest landscape: territorial and administrative boundaries, meeting places, routeways, crossing points and 'central' places. After examining the ways in which these landscape elements helped shape the character of the ancient territory, it considers their conceptual and practical influence on the siting of the region's medieval castles, with a particular focus on sites with their origins in the eleventh to thirteenth centuries. Using Bramber castle as a case study, through existing and new archaeological evidence, including recent analytical earthwork survey and scientific dating, the paper examines in detail the ways in which elements of the natural and cultural world were drawn into an evolving narrative of Norman elite authority. The conclusion is that castles were deliberately sited within much-occupied geographies as part of a deliberate policy aimed at constructing and reproducing claims to territory, power and place.